The DNA Replication Stress Hypothesis of Alzheimer’s Disease - Yuri B. Yurov; Svetlana G. Vorsanova; Ivan Y. Iourov (The Scientific World Journal)
A well-recognized theory of Alzheimer’s disease (AD) pathogenesis suggests ectopic cell cycle events to mediate neurodegeneration. Vulnerable neurons of the AD brain exhibit biomarkers of cell cycle progression and DNA replication suggesting a reentry into the cell cycle. Chromosome reduplication without proper cell cycle completion and mitotic division probably causes neuronal cell dysfunction and death. However, this theory seems to require some inputs in accordance with the generally recognized amyloid cascade theory as well as to explain causes and consequences of genomic instability (aneuploidy) in the AD brain. We propose that unscheduled and incomplete DNA replication (replication stress) destabilizes (epi)genomic landscape in the brain and leads to DNA replication “catastrophe” causing cell death during the S phase (replicative cell death). DNA replication stress can be a key element of the pathogenetic cascade explaining the interplay between ectopic cell cycle events and genetic instabilities in the AD brain. Abnormal cell cycle reentry and somatic genome variations can be used for updating the cell cycle theory introducing replication stress as a missing link between cell genetics and neurobiology of AD.